1998
DOI: 10.1023/a:1011934829263
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The primary mode of thermally induced degradation for this peptide is deamidation. A second degradation mechanism is peptide backbone hydrolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 15 publications
2
15
0
Order By: Relevance
“…Previous findings that the acidic pH and temperature promote Asp dehydration to succinimide explained its higher rate revealed in our experiments. , The loss of ammonia is the first step in Asn deamidation that is completed by hydrolysis of the formed succinimide to Asp or isoAsp in the second step . The literature suggests that at mildly acidic pH, the formation of succinimide is accelerated, whereas the second step is rate-determining, leading thus to the accumulation of succinimide in our experiments. This is in agreement with the increased rate of ammonia loss from Asn at higher temperatures, while the rate of Asn deamidation was not associated with the temperature.…”
Section: Resultssupporting
confidence: 64%
“…Previous findings that the acidic pH and temperature promote Asp dehydration to succinimide explained its higher rate revealed in our experiments. , The loss of ammonia is the first step in Asn deamidation that is completed by hydrolysis of the formed succinimide to Asp or isoAsp in the second step . The literature suggests that at mildly acidic pH, the formation of succinimide is accelerated, whereas the second step is rate-determining, leading thus to the accumulation of succinimide in our experiments. This is in agreement with the increased rate of ammonia loss from Asn at higher temperatures, while the rate of Asn deamidation was not associated with the temperature.…”
Section: Resultssupporting
confidence: 64%
“…Since the activation of both receptors might be advantageous for maximal efficacy on food intake and body weight, we prioritized initially non-selectivity. We found that formulation at pH 7 caused chemical instability including deamidation of asparagine residues, as reported for pramlintide, 17,18 and this could not be solved by formulations or minor pH adjustments. In order not to deviate too much from h-amylin, formulation at low pH seemed necessary, and we initiated a third branch of the program focused on the chemical stability at neutral pH to secure the option of co-formulation with other peptides.…”
Section: ■ Results and Discussionsupporting
confidence: 64%
“…An initial concern was that attachment of a lipophilic fatty acid would increase intermolecular attractive forces, 12−16 causing an even higher propensity to form amyloid fibrils. Additionally, published data on pramlintide 17,18 suggested a need for improvement of chemical stability, primarily targeting deamidation of asparagine residues to enable formulation at neutral pH. The structure−activity relationship (SAR) of amylin in the literature was not very developed at the beginning of our project, but considerable inspiration was available from the differences among amylins 1 from different species, where, for instance, rodent amylins do not form amyloid.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Therefore, assessing the contributions of Asn deamidation to peptide self-assembly also requires targeted residue-specific modifications to obtain mechanistic details at the molecular level. Using pramlintide, a synthetic IAPP derivative used in the clinic, it was reported that five of the six Asn residues are prone to deamidation; Asn-21 and Asn-35 are the most deamidated, whereas Asn-31 is not converted to either aspartic acid or isoaspartic acid. , Herein, we find that modification at position 21 precludes IAPP amyloid assembly whereas deamidation of residue 35 has no significant effect on the kinetics of assembly or fibril morphology. It would be interesting to probe how different combinations of deamidation sites, such as the concurrent N14D and N21D mutations, modulate amyloid formation.…”
Section: Discussionmentioning
confidence: 59%
“…The gluco-modulatory pancreatic hormone islet amyloid polypeptide (IAPP), or amylin, is a 37-residue peptide encompassing six Asn residues (Figure B), and several of these residues can be readily deamidated under physiological conditions. IAPP is an unusual aggregation-prone peptide whose deposition in the form of amyloid fibrils in the islets of Langerhans is associated with type II diabetes . The presence of insoluble IAPP deposits observed in the pancreas is known to accelerate type II diabetes pathogenesis by exacerbating β-cell degeneration and, ultimately, compromising insulin secretion .…”
mentioning
confidence: 99%